Prevalence of Musculoskeletal Symptoms and Assessment of Working Conditions in an Iranian Petrochemical Industry - Alireza Choobineh; Hadi Daneshmandi; Shahed Asadi; Shahram Ahmadi (Shiraz University of Medical Sciences, 2013)
Background/Objective: Musculoskeletal disorders (MSDs) are one of the most common causes of occupational injuries. This study was conducted with the objectives of determination of prevalence rate of MSDs and ergonomics assessment of the risk of MSDs among workers of a petrochemical company. Methods: In this study, 261randomly selected workers in a petrochemical company with at least one year of job tenure participated. Office and operational personnel were studied separately. In office jobs, data were collected using Nordic musculoskeletal disorders questionnaire (NMQ) and ergonomics checklist for assessment of work conditions. In operational jobs, NMQ and QEC (Quick Exposure Check) methods were applied to gather the required data. Data analysis was performed using SPSS software. Results: The most prevalent MSDs symptoms were reported in the lower back (36.2%), upper back (31%), neck (31%) and knees (30.3%). The results showed that the prevalence of MSDs indifferent body regions of the office staff was higher than those of operational workers. Also, in 40.9% of the observed cases, total ergonomics index was in action category 1 (inappropriate working conditions) and 59.9% of the subjects taken in action category 2 (appropriate working conditions). The results of assessment by QEC technique among operational workers showed that in 82.8% of the workers studied, the level of exposure to musculoskeletal risks was high or very high. Conclusions: The prevalence of musculoskeletal disorders in the office staff was higher than that of operational subjects. To improve the working conditions, taking risk factors of the lower back, upper back, neck and knees into consideration seems to be essential.